TINGKAT KESEJAHTERAAN PASANGAN YANG MENIKAH USIA MUDA DI NAGARI SARUASO KECAMATAN TANJUNG EMAS KABUPATEN TANAH DATAR - Marta Sri Devi; Paus Iskarni (DEPARTEMEN GEOGRAFI FIS UNP, 2019)
Abstract This research aims to determine the welfare level of married couples in the young age in Nagari Saruaso District Tanjung Emas District flat land. This type of research is a quantitative descriptive, with a population of all women under the age of 20 who do a young marriage in the year 2006-2018 in Nagari Saruaso that amounted to 102 people. Sampling was taken based on the Purposive Sampling technique and obtained 65 respondents. Data collection techniques through the dissemination of questionnaires or polls and documentation. Analysis techniques using percentage data analysis and scoring techniques. The results showed that the welfare level of married couples is 52 respondents (80%) A moderate level of well-being with a score between 14-19 and 13 respondents (20%) Relatively high score between 20-24. This is due to the family income which is relatively moderate between Rp.1.500.000-Rp.2.500.000 per month, it is high expenditure cost with a large number of family liabilities. The low level of education leads to the difficulty of getting a decent job.